Warna, Kadar Air, Kadar TBA, dan Aktivitas Antioksidan Sup Jangkang (Jagung-Cangkang) Instan Dengan Perbedaan Teknik Kemasan Dan Lama Penyimpanan - Afrilia Arifatul Lael; Siti Aminah; Nurhidajah Nurhidajah (Universitas Muhammadiyah Semarang, 2021)
Instant corn soup is included in the dry form of flour products that have the ability to easily absorb water from the environment (high hygroscopic). Water vapor transfer from the environment can cause quality degradation during storage. The decline in quality triggers chemical, enzymatic or physical reactions to changes in sensory properties. Packaging is known to be able to minimize product quality degradation. The packaging technique can be done by vacuum and non-vacuum techniques. The general objective of the study was to determine the effect of packaging techniques and storage time on the physical and chemical characteristics of instant corn soup enriched with duck eggshell flour. The experimental research method uses factorial completely randomized design (CRD), which consists of 2 factors 8 treatments, namely metallized (vacuum and non vacuum) packaging techniques and storage time (1, 2, 3, and 4 weeks). Each treatment was repeated 4 times, so that 32 units of the experiment were obtained. Data on the results of physical characteristics and chemical characteristics were analyzed using ANOVA statistical methods followed by DMRT advanced tests. The results showed there was an effect of packaging technique and storage time on TBA levels and antioxidant activity, but there was no effect on the color and water content of instant corn soup. Metallized vacuum packaging with 3 weeks storage produced color (13.56%), water content (5.72%), TBA content (0.52 mg MA / kg sample), and antioxidant activity (8,94% RSA).